Comparative Assessment of Outcomes in Drug Treatment for Smoking Cessation and Role of Genetic Polymorphisms of Human Nicotinic Acetylcholine Receptor Subunits - Muderrisoglu, Ahmet; Babaoglu, Elif; Korkmaz, Elif Tugce; Kalkisim, Said; Karabulut, Erdem; Emri, Salih; Babaoglu, Melih O. (Frontiers in Genetics, 2022)
Objective: To investigate the effects of genetic polymorphisms of human nicotinic acetylcholine receptor subunits α3, α4 and α5, which are encoded by CHRNA3, CHRNA4 CHRNA5 genes, respectively, on nicotine addiction and outcomes of pharmacological treatments for smoking cessation. Methods: A total of 143 smokers and 130 non-smokers were included. Genotyping for CHRNA3 rs578776, CHRNA4 rs1044396-rs1044397, CNRNA5 rs16969968 polymorphisms was performed by PCR, flowed by RFLP. Clinical outcomes and success rates of pharmacological treatments for smoking cessation with nicotine replacement therapy (NRT), bupropion or varenicline were determined at the 12th week of the treatment. Results: Overall, 52 out of 143 (36.4%) smokers who received pharmacotherapy were able to quit smoking. Success rates for smoking cessation were similar for female (30.3%) and male (41.6%) subjects (p=0.16). The success rate for smoking cessation treatment with varenicline (58.5%) was significantly higher as compared to other treatments with NRT (20.0%), bupropion (32.3%) or bupropion+NRT (40.0%) (chi-square test, p=0.001). Smoker vs. non-smoker status and the clinical outcomes of drugs used for smoking cessation were found similar in subjects carrying wild-type and variant alleles of human nicotinic acetylcholine receptor α subunits. Conclusion: In this study, smoking cessation treatment with varenicline was significantly more effective than treatments with nicotine replacement or bupropion in a cohort of Turkish subjects. Smoker/non-smoker status and the clinical outcomes of treatment with pharmacological agents were similar in subjects with wild-type or variant alleles for human nicotinic acetylcholine receptor subunits α3 (CHRNA3), α4 (CHRNA4) and α5 (CHRNA5).